Investigation of Different Emissions Tax Calculation Methods for Kuala Lumpur International Airport - Azrin, Alif Izzuddin; Abdul Ghafir, Mohammad Fahmi (Progress in Aerospace and Aviation Technology, 2024)
The aviation sector is among the most active industries globally and has been evolving for over a century. Aviation’s rapid expansion significantly contributes to emissions. This study aims to propose a methodology for calculating nitrogen oxide (NOx) emission taxes for Kuala Lumpur International Airport (KLIA) while concurrently analyzing the departure traffic in the vicinity. This study attempts to identify the airline and differentiate the engine type that contributes to NOx emissions at KLIA. Departure information and aircraft statistics at the specified airport were acquired via FlightRadar 24 and Airfleets.net. The data was collected over a three-month period from September to November 2023. Upon compilation of the collected data, the tax prices are calculated and analyzed using three distinct methodologies. The NOx emission index is derived from the latest version of the ICAO databank. The peak departure hours at KLIA are 9:00 am and 1:00 pm. AirAsia is the airline with the largest daily departure activity, and CFM engines are likely the primary contributors to NOx emissions. Finally, the Copenhagen method is recommended for implementation at KLIA due to its fair and efficient NOx emission tax system, which accurately represents the environmental consequences of its operations and promotes more sustainable behaviors within the aviation sector.